The great fashion designers from Chanel to McQueen, the names that made fashion history - Polan, Brenda; Tredre, Roger (Bloomsbury Visual Arts, 2020)
Over the last 180 years designers have propelled fashion from an elite craft into a cornerstone of popular culture. This brilliantly written guide to the lives and collections of 55 iconic fashion designers draws on the latest academic research and the best of fashion journalism, including the authors' own interviews with designers. Beginning with 19th century couturier Charles Frederick Worth and concluding with the star names of the 2010s, Polan and Tredre detail each designer's working methods and career highlights to capture the spirit of their times. This beautifully illustrated revised edition features five new designer profiles: Hedi Slimane, Raf Simons, Phoebe Philo, Alessandro Michele and Demna Gvasalia. It's also been updated throughout to reflect a fashion world in constant ferment, with designers swapping jobs and fashion houses at unprecedented speed. The industry has expanded into a global phenomenon - and designers have emerged as true celebrities; The Great Fashion Designers explores their passion and flair to show us fashion at its most inspirational.